Analysis of The Effect of Cash Turnover, Inventory Turnover, and Receivables Turnover on Profitability in Manufacturing Companies Listed on The IDX For The 2019-2021 Period - Zhalma Syafitri Alkobar; Subur Karyatun; Kumba Digdowiseiso (CV. Syntax Corporation Indonesia, 2024)
This study aims to find out and analyze whether there is a significant effect of cash turnover, inventory turnover, and accounts receivable turnover on the profitability of manufacturing companies listed on the IDX for the 2019-2021 period. The data used in this study is secondary data, namely the financial reports of manufacturing companies listed on the IDX for the 2019-2021 period. The type of data in this study is quantitative using panel data. The population of this study includes 46 manufacturing companies listed on the IDX for the 2019-2021 period. The sample used is 35 samples. The data analysis used in this study is the model feasibility test method, descriptive analysis, classic assumption test, multiple regression test, and hypothesis testing with panel data using Eviews 10 software. The results showed that the cash turnover variable had no effect on profitability, inventory turnover had a positive and significant effect on profitability, and accounts receivable turnover had a positive and significant effect on profitability.